Two kinds of the positivity of law - Leszczyński, Jerzy (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
Assuming that law should be understood as the positive law exclusively leads to a theoretical problem of how to explain the phenomenon of judicature as something distinct from the positive law. The division between making and applying the law is the reason why the positivity (specificity) of law presents itself differently in those two domains. The positivity of law, as an effect of making the law, is the positivity of law text, whereas the applied law has its positivity in its content. As those two expressions of law positivity are uncomparable, at the same time it allows maintaining a relatively coherent concept of law.